Transdisciplinary Approaches for Market Intelligence Research: Theory, Practice, and Implications for Designing Product Profiles in Crop Breeding - Amoak, Daniel; Najjar, Dina; Belcher, Brian; Connor, Melanie; Banda, Vishnuvardhan Reddy; Teeken, Bela; Muungani, Dean (2023)
The goal of this strategic evidence review is to synthesize and analyze the literature on TDR approaches, with an emphasis on both theory and practice, including research design, team composition, and team dynamics to guide market intelligence research. We seek to highlight the theory behind how TDR works, state-of-the-art TDR project design, and implications for market intelligence TDR in crop breeding. The outcomes of this study add to the body of work seeking to define institutional norms for transdisciplinary teams in developing product profiles in breeding. The findings of this assessment will be valuable for research and development teams at the CGIAR and elsewhere working in agricultural and natural resource management.